Para enegrecer os modos de saber: tecendo identidades em metatextos e intertextos de escritores(as) negros(as) do Brasil (Revista de Crítica Literaria Latinoamericana, 2015)
This article examines the Afrodescendant literature in Brazil today. According to scholars, Latin America was created, on the one hand, by a modern/colonial project, and on the other hand, identity specifications are still on debate. So, it is important to examine Afrodescendant literature as representative of silenced cultures, who, in this context, write of themselves. In the reading and in the analysis of literary texts from Afrobrazilian authors, I demonstrate that metalanguage and intertextuality with literature and history are some aspects of this production.
Keywords: Afrobrazilian literature; Metalanguage; Intertextuality